2003
DOI: 10.1080/13577140310001607293
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Chondromatosis and Chondrosarcoma: A Diagnostic Dilemma

Abstract: Distinction between chondromatosis and its progression to low grade chondrosarcoma is difficult at histological level, and must involve incorporation of clinical and radiographical data. Although preliminary, our study suggests that reduced or absent expression of Bcl2 is associated withmalignant transformation of chondromatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 5 publications
(4 reference statements)
1
44
1
Order By: Relevance
“…Clinically, both may present with pain, swelling and restricted movement of the affected joint with longstanding symptoms. Several authors speculate that a rapid deterioration of a longstanding clinical history or rapid recurrence after synoviectomy may indicate malignant transformation (31,34,53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, both may present with pain, swelling and restricted movement of the affected joint with longstanding symptoms. Several authors speculate that a rapid deterioration of a longstanding clinical history or rapid recurrence after synoviectomy may indicate malignant transformation (31,34,53).…”
Section: Resultsmentioning
confidence: 99%
“…They also indicated that the only MRI criterion of malignancy was the invasion of the bone medullar canal. More recently, in 2003, Sperling et al (31) speculated that the under-expression of the BCL-2 (a cell survival marker) in SCH could be used as diagnostic immunohistochemical tool. Moreover, cytogenetic data can offer important information for the diagnosis and our understanding of the development of SCH from SC.…”
Section: Resultsmentioning
confidence: 99%
“…The most reliable histological sign consists of osseous permeation by cartilage with extension of cartilage matrix into intertrabecular spaces (4, 5, 7). A preliminary study suggests that reduced or absent expression of the immunohistochemical marker Bcl2 is associated with malignant transformation of chondromatosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the immunohistochemistry has not been of much use in differentiating these two conditions. Sperling et al 5 reported that a reduced or absent expression of bcl-2 may be associated with malignant transformation. Their results were in contradiction with the results of Bovee et al 14 who found that bcl-2 expression was significantly higher in low-grade synovial chondrosarcomas than in synovial chondromatosis.…”
Section: Discussionmentioning
confidence: 98%